Price Variability, Utility and Savings - Eaton, Jonathan (Review of Economic Studies, 1980)
Journal Article Price Variability, Utility and Savings Get access Jonathan Eaton Jonathan Eaton Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 3, April 1980, Pages 513–520, https://doi.org/10.2307/2297302 Published: 01 April 1980 Article history Received: 01 November 1977 Accepted: 01 August 1979 Published: 01 April 1980